Fasting, Feasting - Desai, Anita (Gurugram: Penguin Random House, 1999)
A wonderful novel in two parts, moving from the heart of a close-knit Indian household, with its restrictions and prejuices, its noisy warmth and sensual appreciation of food, to the cool centre of an American family, with its freedom and strangely self-denying attitudes to eating. In both it is ultimately the women who suffer, whether, paradoxically, from a surfeit of feasting and family life in India, or from self-denial and starvation in the US. or both. Uma, the plain, older daughter still lives at home, frustrated in her attempts to escape and make a life for herself. Her Indian family is difficult , demanding but mostly, good hearted. Despite her disappointments, Uma comes through as the survivor, avoiding an unfulfilling marriage, liek her sister's or a suicidal one, like that arranged for her pretty cousin. And in America, where young Arun goes as a student, men in the suburbs char hunks of bleeding meat while the women don't appear to cook or eat at all - seems bewildering and terriying to the young Indian adolescent far from home.
Keywords: Fiction -- Women-India -- Families-India- Social life and customs